The Functional & Quality of Life Outcomes of Total Glossectomy with Laryngeal Preservation - Justin M. Pyne; Peter T. Dziegielewski; Gabriela Constantinescu; Agnieszka Dzioba; Daniel A. O'Connell; David W. J. Côté; Khalid Ansari; Jeffrey Harris; Dustin Conrad; Fawaz M. Makki; Matthew Hearn; Vincent L. Biron; et al. (Laryngoscope Investigative Otolaryngology, 2020)
Abstract Background The tongue is an essential organ for human interaction, communication and survival. To date, there is a paucity of objective functional, patient reported, or quality of life outcomes of patients undergoing a total glossectomy with preservation of the larynx (TGLP). Objective To examine prospectively collected objective, self‐reported functional and quality of life (QOL) data in patients undergoing TGLP and free flap reconstruction. Methods Sixteen TGLP patients were identified in the prospective head and neck cancer and functional outcomes database between January of 2009 and December 2017. Data collection included patient age, sex, performance status, TNM staging, diagnosis and adjuvant treatment. Swallowing and speech functions were measured and prospectively recorded pre‐ and postoperatively. Patient reported outcomes were measured with the Speech Handicap Index (SHI) and the M.D. Anderson Dysphagia Inventory (MDADI). Results All patients had a significant reduction in their objective swallowing (P = 0.035), sentence (P = 0.001) and word intelligibility (P < .001) scores. There was no significant reduction in SHI or total MDADI scores. All patients maintained their QOL in the post‐treatment time frame. There was no relationship between free‐flap type and outcome. Conclusion Total glossectomy with laryngeal sparing and free flap reconstruction results in significant reduction in objective functional measurements, but patients report stable functional and quality of life outcomes after treatment.